2001
DOI: 10.1111/j.1477-9552.2001.tb00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Household Demand for Seafood

Abstract: Current changes underway in Spain are likely to lead to changes in demand for different types of seafood products. Double-hurdle models were used to model Spanish household expenditures on these goods, explicitly accounting for the value of women's time in the case of processed seafood goods. The empirical evidence shows that the set of statistically significant factors in the participation and expenditure equations is not the same for fresh and processed seafood goods. The value of women's time (for expenditu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
10
0
3
Order By: Relevance
“…A recent strategy to increase marine product distribution according to new trends in food consumption and lifestyle is represented by the increasing commercialisation of ready-to-eat (RTE) food products, which include a myriad of refrigerated, frozen, cured and canned seafood products (Manrique & Jensen, 2001). Thus, novel and attractive RTE products are increasingly available today in the market and restorer sectors, all of which require strict safety controls and attempt to satisfy the consumer's expectations for taste, flavour and healthiness (Gilbert et al, 2000;Gopinath et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A recent strategy to increase marine product distribution according to new trends in food consumption and lifestyle is represented by the increasing commercialisation of ready-to-eat (RTE) food products, which include a myriad of refrigerated, frozen, cured and canned seafood products (Manrique & Jensen, 2001). Thus, novel and attractive RTE products are increasingly available today in the market and restorer sectors, all of which require strict safety controls and attempt to satisfy the consumer's expectations for taste, flavour and healthiness (Gilbert et al, 2000;Gopinath et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as expected, the household behaviour of expenditures on food is directly related to the household size. Previous studies have estimated that there exists a positive relationship between the number of members in a household and the level of its expenditures on food (García and Grande 2010;Heien et al 1989;Jacobson et al 2010;Jae et al 2000;Manrique and Jensen 1998). The previous study of Karagiannis and Velentzas (1997) found that Greek consumers have tended to reduce their consumption of bread and cereals over time but have increased their consumption of all other food items, with the most striking changes occurring in the consumption of meat and livestock products, such as milk, cheese and eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these have focused on household consumption by investigating food purchasing (Büchs and Schnepf 2013;Jones and Kammen 2014;Zezza et al 2017). Particular studies have been conducted to analyse the socioeconomic determinants and demographic factors of food spending (Capps and Love 1983;Davis et al 1983;Heien et al 1989;Fan et al 1994;Kinsey 1994;Nayga 1995;McDowell et al 1997;Manrique and Jensen 1998;Jae et al 2000;Sabates et al 2001;Ghany et al 2002;Gould 2002;Raper et al 2002;Kirkpatrick and Tarasuk 2003;Ricciuto et al 2006;Jacobson et al 2010;Barigozzi et al 2012;Kostakis 2014;Damari and Kissinger 2018;Hidaka et al 2018;Janssen 2018;Marques et al 2018).…”
Section: A Brief Literature Review On Food Behaviormentioning
confidence: 99%
“…In contrast, the presence of ahgA , porphyranase and agarase genes in a minority of Spanish individuals is unlikely to be explained by an HGT promoted by the consummation of edible seaweeds. However, seafood has always been prominent in traditional Spanish gastronomy (Medina, 2005) and Spain is among the largest consuming nations of seafood in the world (Manrique and Jensen, 2001). As we have proposed above for the symbiotic firmicutes, a possible explanation is that Spanish gut bacteria acquired ahgA and related genes from ancestral agarolytic marine bacteria attached to seafood of animal origin.…”
Section: Discussionmentioning
confidence: 99%